2012
DOI: 10.1002/jbmr.1612
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness-related bone loss is associated with osteoclastic and angiogenic abnormalities

Abstract: Critically ill patients are at increased risk of fractures during rehabilitation, and can experience impaired healing of traumatic and surgical bone fractures. In addition, markers of bone resorption are markedly increased in critically ill patients, while markers of bone formation are decreased. In the current study, we have directly investigated the effect of critical illness on bone metabolism and repair. In a human in vitro model of critical illness, Fluorescence-activated cell sorting (FACS) analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Our findings are also indicative of altered bone turnover in a selected population of critically ill patients which is consistent with current literature showing an association between the duration of critical illness (>5 days) and bone resorption [1, 10]. This BTMs pattern is consistent with previous studies that reported increased bone resorption markers [4, 814], increased serum osteoclast precursors [15], increased bone formation, and decreased osteocalcin during critical illness compared with controls [4, 11, 16]. These studies consistently described changes: an increased osteoclastic bone resorption (increased urinary DpD and PyD, serum B-CTX/ICTP), an increase in immature osteoblast number and activity (serum P1CP and PINP), and a reduced activity of mature osteoblasts (serum OC and ALP) [4, 8, 1017].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also indicative of altered bone turnover in a selected population of critically ill patients which is consistent with current literature showing an association between the duration of critical illness (>5 days) and bone resorption [1, 10]. This BTMs pattern is consistent with previous studies that reported increased bone resorption markers [4, 814], increased serum osteoclast precursors [15], increased bone formation, and decreased osteocalcin during critical illness compared with controls [4, 11, 16]. These studies consistently described changes: an increased osteoclastic bone resorption (increased urinary DpD and PyD, serum B-CTX/ICTP), an increase in immature osteoblast number and activity (serum P1CP and PINP), and a reduced activity of mature osteoblasts (serum OC and ALP) [4, 8, 1017].…”
Section: Discussionsupporting
confidence: 92%
“…A further six studies were identified for full-text review from a manual search of citation lists. Of the 27 fulltext studies reviewed, 16 were excluded for not meeting the predetermined eligibility criteria, resulting in 11 studies included in the final analysis [18][19][20][21][22][23][24][25][26][27][28]. In three of the case-control studies, ICU patients were randomised to an intervention after comparison of baseline data from the ICU cohort was compared to a control cohort [22, 23,26].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The baseline data from these studies was included in the analysis, whereas the data resulting from the randomised intervention was excluded. One study performed in-vivo analysis of osteoclast number and activity in ICU patients compared to controls, with further in-vitro analysis of osteoclast cells, osteoblastic cells, and serum activation factors [25]. As the in-vitro tests were not recognised tests of bone turnover, they were excluded from the analysis.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this potential influence of EPC on bone formation, the common origin of EPC and osteoclast precursor cells also bears a risk that mononuclear cells (MNC) or EPC transdifferentiate into mature osteoclasts. We used CD11b as a marker for myeloid cells which has been also used to characterize circulating osteoclasts precursors or mature osteoclasts . In accordance with these observations mice suffering from osteopetrosis treated by blood derived mononuclear cells reveal a transient contribution of these cells to the osteoclast populations of treated animals .…”
Section: Discussionmentioning
confidence: 69%